A night in Terror Tower - Stine, R. L. (New York : Scholastic, 1995)
While visiting London, Sue and her brother get separated from the tour group and find themselves trapped in a prison tower and transported back in time.
3.5
5-8
Keywords: Castles -- Juvenile fiction; Castles -- Fiction; Horror stories; Castles -- Fiction; Horror fiction; Great Britain -- History -- Medieval period, 1066-1485 -- Juvenile fiction; Great Britain -- History -- Medieval period, 1066-1485 -- Fiction; Great Britain -- History -- 1066-1485, Medieval period -- Fiction; Horror fiction